Convergence Science to Transform Biomedicine: A Narrative Review - Moslem BAHADORI; Seyed Mahdi REZAYAT SORKHABADI; Dariush D FARHUD; Soheila FAZLI TABAEI (Tehran University of Medical Sciences, 2020)
Recently convergence science was proposed and promoted in a large report from US National Science Foundation and Department of Commerce (NSF/DOC). The report was entitled "converging technologies for improving human performance. "It was dealing with converging of four technologies as: Nanotechnology, Biotechnology, Information technology and Cognitive science (NBIC). The report has gained tremendous popularity throughout the academia and scientific world. On Dec 2015 in a monthly meeting of the department of basic science of Iran Academy of Medical Science, the report of NSF/DOC on NBIC has been discussed. A working group has been established for more discussion and application in Iran. Several seminars in this regard have been performed, and presently this technology has been started as pilot in some technical universities in Iran. After US National Research Council (NCR) in the year 2014 and Massachusetts Institute of Technology (MIT) on convergence in biomedicine, the concept opened a new gate to approach solving medical and health care problems; the convergence technology in biomedical sciences has become interested and gained great popularity among the working group of convergence science in academy of medical science. This technology can lead to advances in fighting chronic diseases such as cancer, dementia, psychiatric disorders, disease of aging and others. The following is summary of proposed discussions in several gathered groups of scientists in this field.